Validating Automotive Control Software Using Instrumentation-Based Verification - Ray, A.; Morschhaeuser, I.; Ackermann, C.; Cleaveland, R.; Shelton, C.; Martin, C. (2009 IEEE/ACM International Conference on Automated Software Engineering, 2009)
This paper discusses the results of an application of a formally based verification technique, called Instrumentation-Based Verification (IBV), to a production automotive lighting controller. The goal of the study is to assess, from both a tools as well as a methodological perspective, the performance of IBV in an industrial setting. The insights obtained as a result of the project include a refinement of a previously developed architecture for requirements specifications; observations about changes to model-based design workflows; insights into the role of requirements during development; and the capability of automated verification to detect inconsistencies among requirements as well as between requirements and design models.